Systematic Literature Review on Blockchain-Based Knowledge Integration Models for Higher Learning Institutions - Nur Ilyana Ismarau Tajuddin,; Izni, Nor Aziyatul; Nurafifah Mohd Nor,; Sudin, Muhammad Nuruddin; Mohd Anim, Nur Aqilah Hazirah; Rozi Nor Haizan ,; Md Noor, Noorashikin; Khairi Azhar Aziz, (Journal of Technology Management and Business, 2025)
This paper presents a systematic literature review (SLR) on the knowledge integration (KI) of blockchain technology within higher learning education institutions (HLI), focusing on the development of a comprehensive model. With the growing importance of blockchain in various sectors, its potential applications in higher education, particularly in areas like data management, credentialing, and academic integrity, warrant an in-depth exploration. This SLR examines existing literature from academic databases, analyzing studies that discuss blockchain's role and potential in educational contexts. The review synthesises findings across various dimensions, including blockchain's advantages, challenges, and the requirements for effective integration within institutional frameworks. Thirty-three studies from 2020–2024 that were found in Scopus, Science Direct, and Google Scholar satisfied the study's requirements. Using the PRISMA paradigm, this study looked at a number of literature review components, such as subject area, research approach, and research type. This article's conclusion offers guidance for next research. By addressing both opportunities and challenges, this research contributes a framework to guide educational institutions in leveraging blockchain technology for enhanced knowledge management, data security, and operational efficiency. The paper concludes with recommendations for future research and practical guidelines for administrators and policymakers considering blockchain integration within educational environments.